A Positively Embodied Approach to Psychotherapy. Issue 1 (3rd April 2019) - Scott, Elizabeth
Abstract: This article introduces a practical model for therapists to promote recovery from eating and body image problems in their clients. The history of The Body Positive, a nonprofit eating disorders prevention organization that addresses the impact of gender and other intersecting identities on body image, is shared. Five competencies are offered that were developed through The Body Positive's feminist-informed process of dialog with students engaged in activism against sizeism in their communities. The competencies (Reclaim Health, Practice Intuitive Self Care, Cultivate Self Love, Declare Your Own Authentic Beauty, and Build Community) offer resources to support therapists to model an alive, attuned relationship to their own bodies as well as skills to guide their clients to a kinder and more passionate embodiment.